Mesenchymal stem cells and oncolytic viruses: joining forces against cancer. Issue 2 (8th February 2021) - Moreno, Rafael
Abstract : The development of oncolytic viruses (OVs) has increased significantly in the past 20 years, with many candidates entering clinical trials and three of them receiving approval for some indications. Recently, OVs have also gathered interest as candidates to use in combination with immunotherapies for cancer due to their immunogenic properties, which include immunogenic cell death and the possibility to carry therapeutic transgenes in their genomes. OVs transform non-immunogenic 'cold' tumors into inflamed immunogenic 'hot' tumors, where immunotherapies show the highest efficacy. However, in monotherapy or in combination with immunotherapy, OVs face numerous challenges that limit their successful application, in particular upon systemic administration, such as liver sequestration, neutralizing interactions in blood, physical barriers to infection, and fast clearance by the immune system. In this regard, the use of mesenchymal stem cells (MSCs) as cells carrier for OV delivery addresses many of these obstacles acting as virus carriers and factories, expressing additional transgenes, and modulating the immune system. Here, I review the current progress of OVs-loaded MSCs in cancer, focusing on their interaction with the immune system, and discuss new strategies to improve their therapeutic efficacy.